DEVELOPMENT OF THE HEALTH CARE SYSTEM IN ADJARA NEW APPROACH TO MANAGEMENT - Batiashvili, Gogi; Gerzmava, Otar; Bolkvadze, Roman (European Scientific Journal, ESJ, 2014)
The purpose of this paper is to study urgent pathology expansion peculiarities in the Autonomous Republic of Adjara, taking into account the social background of patients, and information about their working and social conditions. This paper will also study the complex valuation of preventive, curative, and aftercare medical aid potency, together with the framing and implementing of scientifically proven practical recommendations on the basis of the research results. In most cases, these diseases receive practically no conservative treatment and need urgent medical interference, yet patients do not admit themselves to hospitals in sufficient time for treatment because of possible expenses. It is without question that charges for belated treatment of urgent pathology are too high, not only for a patient’s family, but for the budget of public health. This situation causes serious problems in the social and medical financing of the growing population. It should be noted that the cause for delay of medical interference is not just a financial problem, but an issue of a low literacy level, peculiarities in the flow of disease, transportation problems, etc.